Functional effects of KCNQ K+ channels in airway smooth muscle - Evseev, Alexey I.; Semenov, Iurii; Archer, Crystal; Medina, Jorge; Dube, Peter H.; Shapiro, Mark S.; Brenner, Robert (Frontiers in Physiology, 2013)
KCNQ (Kv7) channels underlie a voltage-gated K+ current best known for control of neuronal excitability, and its inhibition by Gq/11-coupled, muscarinic signaling. Studies have indicated expression of KCNQ channels in airway smooth muscle (ASM), a tissue that is predominantly regulated by muscarinic receptor signaling. Therefore we investigated the function of KCNQ channels in rodent ASM and their interplay with Gq/11-coupled M3 muscarinic receptors. Perforated-patch clamp of dissociated ASM cells detected a K+ current inhibited by the KCNQ antagonist, XE991, and augmented by the specific agonist, flupirtine. KCNQ channels begin to activate at voltages near resting potentials for ASM cells, and indeed XE991 depolarized resting membrane potentials. Muscarinic receptor activation inhibited KCNQ current weakly (~20%) at concentrations half-maximal for contractions. Thus, we were surprised to see that KCNQ had no affect on membrane voltage or muscle contractility following muscarinic activation. Further, M3 receptor-specific antagonist J104129 fumarate alone did not reveal KCNQ effects on muscarinic evoked depolarization or contractility. However a role for KCNQ channels was revealed when BK-K+ channel activities are reduced. While KCNQ channels do control resting potentials, they appear to play a redundant role with BK calcium-activated K+ channels during ASM muscarinic signaling. In contrast to effect of antagonist, we observe that KCNQ agonist flupirtine caused a significant hyperpolarization and reduced contraction in vitro irrespective of muscarinic activation. Using non-invasive whole animal plethysmography, the clinically approved KCNQ agonist retigabine caused a transient reduction in indexes of airway resistance in both wild type and BK β1 knockout mice treated with the muscarinic agonist. These findings indicate that KCNQ channels can be recruited via agonists to oppose muscarinic evoked contractions and may be of therapeutic value as bronchodilators.